Systemic treatment of recurrent and/or metastatic squamous cell carcinomas of the head and neck: what is the best therapeutic sequence?. Issue 3 (May 2022) - Saada-Bouzid, Esma; Peyrade, Frederic; Guigay, Joël
Abstract : Purpose of review: The treatment of recurrent and/or metastatic head and neck squamous cell carcinoma patients is revolutionized by the advent of anti-PD1 checkpoint inhibitors. Recent findings: Indeed, Pembrolizumab is approved as monotherapy or used in combination with platin and fluorouracil for first-line patients with tumors expressing PD-L1. Nivolumab and Pembrolizumab are also approved in second line of recurrent/metastatic head and neck squamous cell carcinoma. Moreover, the substitution of fluorouracil for a taxane in the TPEx regimen has shown improvement in safety profile when compared with EXTREME regimen. Summary: Here we carry out a review of the main results of pivotal trials and discuss the pros and cons of the three possible scenarios when considering the therapeutic sequence (first and second line).